Systematic Review of Psychological and Behavioral Correlates of Recreational Running - Pereira, Hugo Vieira; Palmeira, António Labisa; Encantado, Jorge; Marques, Marta Moreira; Santos, Inês; Carraça, Eliana Veiga; Teixeira, Pedro J. (Frontiers in Psychology, 2021)
Introduction: The aim of this review was to systematically synthesize the published literature describing the psychological and behavioral correlates of recreational running in adults, defined as running for leisure, with or without a competitive component. Methods: Quantitative research published in peer-reviewed journals until January 2021 were included. Studies were identified through MEDLINE, PsycINFO, SPORTDiscus, and Web of Science, and were included in this review if they 1) were aimed at recreational running, 2) included a general adult samples (18 years or older, without a diagnosed medical condition or metabolic disorder), and 3) assessed psychological or behavioral correlates of recreational running. Results: Fifty-six articles reporting 58 studies met the eligibility criteria and were included. There were 27 cross-sectional studies, 12 longitudinal studies, and 19 trials (8 non-controlled trials, 5 controlled trials and 6 randomized controlled trials) (n = 37501, 18 to 77 years old, 43% women). Twenty-eight studies assessed antecedents of running behavior, and 25 studies used running behavior as treatment or predictor of a given effect or outcome. Four studies examined both predictors and outcomes of running. Thirty-one studies showed poor quality, while 20 had fair and 7 good quality. Motives were the most frequently studied antecedent of running behavior (k = 19), and results suggest that the highest ranked or more prevalent motives were physical health, psychological motives, and personal achievement. Additionally, perceived control, attitude towards running, intention and subjective norms, self-efficacy and social support may also played a role in the adoption of recreational running. Moreover, improvements in mood (k = 10) and wellbeing (k = 10) were the most frequently reported positive outcomes of running. Reductions in depression, anxiety, and stress were also reported in included studies. Discussion: To our knowledge, this is the first systematic review on this topic. The identification of behavioral and psychological correlates of recreational running across populations can contribute to inform and guide a public policy agenda, focused on helping people sustain regular physical activity, through a modality they have chosen and appear to enjoy.